Desenvolvimento de sensor baseado em polímero molecularmente impresso e nanopartículas - Alvarenga, Laís Mendes (2022)
Metronidazole (MNZ) is a potent antibiotic that, for over 55 years, has been widely used around the world to treat bacterial, amoeba and protozoan infections. Several studies show that the accumulation of this drug in the body can cause toxic, carcinogenic reactions and/or promote the dissemination of bacteria resistant strains, and therefore, maintaining a high level of control of residual concentrations of this drug in aqueous matrices is vital for the public health. The detection of MNZ has generally been performed by high-cost analytical techniques such as gas chromatography coupled to a mass spectrometer (GC/MS) and high-performance liquid chromatography (HPLC), which require time and skilled labor to perform the analyses. Thus, the production of composites sensors capable of detecting and selectively extracting residues of this antibiotic in aqueous matrices has great potential for application in monitoring MNZ concentrations with reduced costs, speed and simplicity of the process. In this work, the preparation and characterization of fluorescent and magnetic composites based on molecularly imprinted (MMIP@PQs) and unprinted (MNIP@PQs) polymers was performed and the materials obtained were evaluated in optical MNZ extraction- detection processes in aqueous media. The MIPs and NIPs were prepared in the presence of thioglycolic acid coated cadmium telluride quantum dots (PQs) (CdTe@TGA) and magnetite nanoparticles (NPMs) coated with tetraethoxysilane (Fe 3 O 4 @TEOS). Analysis by isothermal titration calorimetry indicated that the ideal molar ratio between MNZ and the functional monomer in the preparation of MIPs was 1:4. In addition, with the calorimetric studies, the thermodynamic parameters , , e , e were determined, which proved how favorable interactions are between MNZ and APTES. All the prepared materials were extensively characterized by spectroscopic and electron microscopy techniques. The sensitivity of the composites prepared was studied at different concentrations of MNZ (0 to 60 μM), the MIP presented a detection limit for MNZ of 1.25 μM, being 2 times more sensitive than the NIP. The selectivity of the sensors was evaluated against two other interferents and the MIP proved to be highly selective, as it practically did not suffer queching in the presence of the interferents, while the NIP did. Finally, kinetic studies showed that MIP is able to detect trace concentrations of MNZ in the first minute of analysis, with high selectivity and without the need for previous sample preparation.